Ketuban pecah dini, partus prematurus imminens, penatalaksanaan - Prizka Putri Pahlawan; Rika Lisiswanti; Anggraeni Janar Wulan; Merry Indah Sari (CV. Jasa Sukses Abadi, 2020)
The growth of social media usage has increased almost 15 times, in line with the growth of internet usage in Indonesia in the last 10 years. Social media usage has a relationship with learning motivation, even though long duration of social media usage has impact on the decrease of learning motivation. Investigated relationship of social media usage duration with student learning motivation in class of 2015 Faculty of Medicine, the University of Lampung. Cross sectional design was applied in this research by taking primary data during period of August to September 2017, with the sample of 185 students class of 2015 Faculty of Medicine, the University of Lampung. Analysis model used was Chi-Square Analysis. Based on the statistic value of significant alpha more than 0,05, there was no relationship between social media usage duration and learning motivation. Moreover, the research result shows that learning motivation in term of intrinsic dimension was in low category with the amount of 55,14%. Beside this, leaning motivation in term of extrinsic motivation external regulation was in high category with the total amount of 56,76%. The duration of the use of social media has a positive relationship on student learning motivation because the duration of the use of social media by students of the Faculty of Medicine, University of Lampung class of 2015 is less than one hour per day and student learning motivation is in the aspect of extrinsic motivation of external regulation.